A gasket-type standard leak element using femtosecond laser micromachining. (October 2020) - Chan, C.K.; Tu, C.Y.; Yeh, S.D.; Chang, C.C.; Lin, T.C.; Luo, C.W.; Hwang, C.S.
Abstract: A gasket-type standard leak element with a microfluidic channel was developed and measured. The microfluidic channel with a diameter of several micrometers and a length of one hundred micrometers was fabricated by using femtosecond laser micromachining. The conductances (<1 × 10 −6  L s −1 ) of the microfluidic channel for various non-condensable gases -- H2, He, CH4, N2 and CO2 were determined by a measuring system based on conductance modulation (CM) method. The experimental results show that the flow characteristics of our devices exhibit molecular flow at a pressure up to 100 mbar and the conductance values of H2, He, CH4, N2 and CO2 are inversely proportional to the square root of their molecular mass. Highlights: A gasket-type standard leak element with a microfluidic channel was developed. A tiny conductance of about 4 × 10 −8  L s −1 for N2 can be achieved. A strong dependence of the conductance on the inverse square root of the molecular mass was observed in this device.